Effect of the Subprime Crisis on Return and Volatility of the Turkish Stock Market - Sekmen, Taner (Journal of Economics and Behavioral Studies, 2015)
The aim of this paper is to investigate the return and volatility behaviors of the Turkish Stock Exchange in response to the mortgage crisis using daily observations for the period June 2004 to June 2014. The data are divided into three sub-periods to allow for the investigation of the behavior of the stock market during each sub-period. We employ the GARCH, EGARCH and GARCH-M models to capture volatility. The results indicate that the subprime crisis both induced a notable increase in volatility and changed the relationship between risk and expected return on the Turkish Stock Exchange.